Macrophyte Occurrence in Response to Anthropogenic Pressure in Reservoir - Carla Denise Tedesco; Claudia Petry; Edson Campanhola Bortoluzzi; Alfredo Castamann (Fronteiras: Journal of Social, Technological and Environmental Science, 2017)
The objective of this study was to evaluate the effect of anthropogenic land use on the community of aquatic plants in the vicinity of a consolidated artificial reservoir. Two landscape units (LU) were outlined adjacent to a more than 50-year-old artificial reservoir, of which one (LU1) had a low and the second (LU2) a high human impact. In total, we found 20 plant species. Only two species were common to UP1 and UP2. The species diversity in LU1 (n=18) was greater than in LU2 (n=4), and plant distribution more even. Phosphorus, potassium, organic matter, calcium, and magnesium contents were lower in LU2. It can be concluded that the embankment induced the occurrence of more macrophyte species and plants, due to the soil conservation in the reservoir surroundings. The low human impact in this area allowed a greater diversity of native macrophytes. The intensification of land use around the reservoir impoverishes the soil, preventing the development of a diversified community of macrophyte.